2012
DOI: 10.2169/internalmedicine.51.7748
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia Associated with a Proton Pump Inhibitor

Abstract: Severe hypomagnesemia is a serious clinical condition. Proton pump inhibitor (PPI) induced hypomagnesemia has been recognized since 2006. In March 2011 the U.S. Food and Drug Administration advised that long-term use of PPI can induce hypomagnesemia. We report the first Japanese case of hypomagnesemia associated with chronic use of PPIs in a 64-year-old man hospitalized for nausea, bilateral ankle arthritis, and tremor of the extremities who had convulsions 3 days after admission. Blood analysis showed severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Yet, significant differences (p<0.05) between female consumers and no consumers were found in all variables, supporting findings from van der Hoorn study (30), and suggesting that the prescription of A02B medication group should be especially careful when prescribing in middle aged or elderly females. We believe that significant differences (p<0.05) found in Hand grip isometric muscle strength in total and in gender based, could be linked to the possible association between PPI usage and hypomagnesemia which is related to muscle cramps, something that has been proofed previously by Furlanetto & Faulhaber and Matsuyama et al (31, 32). …”
Section: Discussionsupporting
confidence: 61%
“…Yet, significant differences (p<0.05) between female consumers and no consumers were found in all variables, supporting findings from van der Hoorn study (30), and suggesting that the prescription of A02B medication group should be especially careful when prescribing in middle aged or elderly females. We believe that significant differences (p<0.05) found in Hand grip isometric muscle strength in total and in gender based, could be linked to the possible association between PPI usage and hypomagnesemia which is related to muscle cramps, something that has been proofed previously by Furlanetto & Faulhaber and Matsuyama et al (31, 32). …”
Section: Discussionsupporting
confidence: 61%
“…However, most studies suggest that PPIs likely do not affect vitamin D status [36].The major function of Mg is in bone formation and in ATP reactions [37]. Several articles report hypomagnesemia in long-term PPI treatment [38][39][40][41]. A recent meta-analysis article also reported that PPI use is associated with increased odds of hypomagnesemia, perhaps due to PPIs "aggravating" the TRPM6/TRPM7 genes that may lead to decreased magnesium intestinal absorption [42].…”
Section: Possible Mechanisms For Nutritional Deficiencies Associamentioning
confidence: 99%
“…The DRIs also suggest that Mg intake is low, absorption is decreased, and urinary Mg is increased in elderly people [37]. Therefore, the monitoring of serum magnesium levels should be considered in patients with chronic use of PPIs or GERD, since it is likely that there is a dose-response relationship [38,42]. The current treatment for hypomagnesemia associated with PPIs is magnesium supplementation and discontinuation of the PPI.…”
Section: Possible Mechanisms For Nutritional Deficiencies Associamentioning
confidence: 99%
See 1 more Smart Citation
“…Međutim, poslednjih nekoliko godina se često prijavljuju slučajevi hipomagnezemije pri dugotrajnoj terapiji IPP, nakon što je u martu 2011. godine FDA ukazala na ovaj problem [41]. Hipomagnezemija može proticati asimptomatski, ili izazvati različitu simptomatologiju, od nauzeje, preko mišićnih spazama, artritisa, tremora, pa do konvulzija [42][43][44] . Nastala hipomagnezemija, praćena je i hipokalcemijom, kao i hipoparatireoidizmom [45,46].…”
Section: Potencijalni Rizici Primene Inhibitora Protonske Pumpeunclassified